Socio-cultural projects: narrative techniques of marketing communications - Olesya A. Blinova; Evgeny Yu. Seidyafarov (Управление культурой)
The need for systematic change in the socio-cultural environment generates a need for project activities in a person. The authors of the work consider a socio-cultural project as a social practice aimed at qualitative transformation of the surrounding reality and the person himself. As a strategy for managing a socio-cultural project, the strategy of socially responsible marketing is considered, according to which marketing performs not only economic tasks related to the promotion, positioning or branding of an organization, but also social ones, where the basis is attracting attention to solving socially significant problems and issues. The authors assert the narrative nature of socially responsible marketing, according to which correctly presented information about an event allows giving reality the necessary meanings, which gives rise to the necessary emotions in the recipient, contributing to his involvement in the events of the project. The narrative nature of socially responsible marketing is best realized through the technique of narrative study, namely, through the formulation of a marketing message in the format of a story, a personal story, storytelling. This format allows you to create your own message for different segments of the target audience, has a virulent nature, which allows it to quickly spread across the network and get the largest coverage, and, therefore, be more effective. Within the framework of the article, the effectiveness of the narrative study was tested through the implementation of the project "Spring is the season of volunteering" (project manager - E. Yu. Seydyafarov), the purpose of which was, on the one hand, to promote the International Public Organization "Boxing Federation named after Master of Sports of the USSR S. V. Romanov, Pervouralsk", and on the other hand, to attract public attention to such social problems as donation, helping homeless animals and the cleanliness of public spaces. To inform and invite to participate, narrative study tools were used - short tweets and "reels". These tools turned out to be more effective, since they were recorded for each category of residents separately, Internet users left their reactions under publications, made reposts, which contributed to significant coverage. Thanks to the chosen marketing strategy, events that rarely resonate with city residents gathered a sufficient number of participants, some of whom became volunteers of partner organizations. In conclusion, the work concluded that the narrative study technique and the strategy of socially responsible marketing are effective, provided that the work is systematic and long-term.